Job shopping after vocational training? An empirical analysis of the transition from apprenticeship training to work - Wolfgang Franz; Volker Zimmermann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This econometric study deals with the question as to what extent apprentices after successfully completing their training stay with the firm where they have received their training and, if so, how long that job tenure holds. Determinants of both decisions can be seen from both the employer`s and the employee`s viewpoint. The firm is interested to employ this apprentices in order to collect the returns from its investment in their training which frequently is associated with net costs. On the other hand, the firm dismisses apprentices if training is viewed by the firm as a screening device or if apprentices are engaged in work for which, in terms of wages, they are too expensive afterwards. The young trained worker bases his or her decision to stay or to leave on considerations such as experimenting with several jobs ("job shopping"). The realization of such an experimenting may depend on the situation on the labour market. The empirical part uses individual employee data covering the time period 1980 to 1991 in West Germany and is based on a hazard rate model.
Keywords: J41; J63; J62; 330; Training; Apprenticeship; Youth Unemployment; Matching; Auszubildende; Berufseinstieg; Betriebszugehörigkeit; Arbeitsmobilität; Matching; Jugendarbeitslosigkeit; Bildungsökonomik; Deutschland